Tari Jaran Endut, dari Cerita Rakyat ke Tari Kontemporer - Putu Gita Rahayu Putriandini; I Gusti Ngurah Sudibya; Ida Ayu Wayan Arya Satyani (Jurnal IGEL : Journal Of Dance, 2021)
Jaran Endut Dance is a contemporary dance originating from the folklore of West Nusa Tenggara. Raising the history of the formation of Dusun Endut from the privilege of a horse. The idea of working on this work is the spirit of Jaran Endut in his long journey of helping the people of Pejarakan. The theme used is toughness. Toughness is manifested in the agility, dexterity, sharpness, and speed of the horse in moving. The creator felt challenged to bring an animal character; horse, into the human body. Visualizing the character of a horse requires agile body movements, expression and character deepening, so that the characteristics of the Jaran Endut dance can be conveyed. In addition, "silence" in Jaran Endut's work requires strong energy and physical strength so that the message can be conveyed properly. Humans do have to work hard, but silence is also important in order to choose the next step. The stages of manufacture use the Alma, M. Hawkins creation method, namely the exploration, improvisation, and forming. The structure of the dance work consists of sections 1, 2, and 3, with the form of a large group consisting of eight dancers who have close to compact body postures, thus showing the impression of moving. Accompanied by dance music in the form of MIDI by combining traditional and digital music so that the uniqueness of Jaran Endut I dance music appears. After this process has been running for 1 year, finally this work can be realized with the title of Jaran Endut (Motionless Horse)Keywords: Jaran Endut, Horse Character, Toughness